THE USE OF BILINGUAL SIGNS IN BEKASI CITY TRAIN STATION: A STUDY OF LINGUISTIC LANDSCAPE - Aryani, Lilis; Indah, Rohmani Nur (Universitas Suryakancana, 2025)
This study aims to explore the effectiveness of the use of bilingual signs in facilitating communication and navigation for passengers at Bekasi Train Station. Specifically, this study aims to answer two questions namely, what is the linguistic appearance of the top-down and bottom-up bilingual signs in Bekasi station, and how does the linguistic landscape of the signs function? The method used in this study is qualitative with observation and interview approaches. Data was collected through photo documentation of language signs present at the station and interviews with station officers as well as users. These signs were analyzed by categorizing them into top-down (issued by official authorities) and bottom-up (issued by individuals or the private sector) signs. Further analysis was conducted to explore the sign function. The results show that most of the signs at Bekasi Station are bilingual using both Indonesian and English, with Indonesian being more dominant in font size. The function of signs is identified through two main perspectives, namely informative function and symbolic function. The informative function is seen from signs that assist passengers in navigation and service understanding, while the symbolic function reflects the identity and power of the signage, such as official government signs that assert authority in the management of public transportation. Overall, this study reveals that the use of bilingual signs at Bekasi station reflects the need for effective communication for users from different language backgrounds and provides an in-depth look at the dynamics of language use in the context of public space